Beyond the "SP" label : improving the spelling of learning disabled and basic writers - McAlexander, Patricia J.; Dobie, Ann B.; Gregg, Noel. (Urbana, Ill. : National Council of Teachers of English, 1992)
Provides educators with tips for helping students with learning disabilities and basic writers improve their spelling skills.
Includes bibliographical references (p. 86-89).
Professional
Keywords: English language -- Orthography and spelling -- Study and teaching -- United States; English language -- Remedial teaching -- United States; English language -- United States -- Remedial teaching; English language -- United States -- Spelling -- Study and teaching